16. THE CURRENT STATUS OF THE QUALITY OF CERVICAL CYTOLOGY SPECIMENS IN PATIENTS ATTENDING EXAMINATIONS AT TU DU HOSPITAL, HO CHI MINH CITY, AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objectives: Description of the current situation and some related factors affecting the quality of cervical cytology specimens in patients attending examinations at Tu Du Hospital, Ho Chi Minh City in 2023. Subjects and research methods: Cross-sectional study describing patients attending examinations at Tu Du Hospital. Results: Sample quality passed (93.4%), failed (6.6%). There is a relationship between the quality of the test sample and the patient’s menstrual cycle, history of vaginal bleeding/abnormal discharge other than the menstrual cycle, lower abdominal pain, and diagnosis of uterine vaginitis, patient samples are preserved and processed according to regulations, the department performing sampling, chemicals are guaranteed, all types of Pap testing techniques and staining techniques are guaranteed. Conclusions: It is noted that sample quality is quite high, however, it is necessary to regularly monitor the knowledge and professional skills of staff and strengthen communication education about Pap smear testing in the community.
Keywords: Cervical cancer, cytology test, Tu Du Hospital.